A biological glass-containing wound-protecting ointment, dressing and preparation method thereof

CN122376816BActive Publication Date: 2026-10-16XIEHE HOSPITAL ATTACHED TO TONGJI MEDICAL COLLEGE HUAZHONG SCI & TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610881686.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-10-16
Estimated Expiration
2046-06-17

AI Technical Summary

Technical Problem

[0005]本申请提供一种含生物玻璃护创药膏、敷贴及制备方法,以解决相关技术中生物玻璃颗粒与高分子基体界面相容性差,容易发生生物玻璃的离子突释或完全不释现象

Benefits of technology

本申请实施例提供了一种含生物玻璃护创药膏、敷贴及制备方法,本申请通过低玻璃化转变温度氢键网络构建、生物玻璃钙离子表面改性、凡士林杂化乳化,实现生物玻璃与基体强界面结合,离子可控释放,剥离强度达3N/cm以上,兼具止血、封闭、抗菌、促愈功效,解决传统生物玻璃敷贴相容性差、离子释放失控、剥离易二次创伤的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122376816B_ABST
    Figure CN122376816B_ABST
Patent Text Reader

Abstract

The application relates to a biological glass-containing wound-care ointment, a dressing and a preparation method, which comprises the following steps: uniformly stirring betaine and tannic acid to obtain a low glass transition temperature mixture; adding biological glass into a CaCl2 solution, uniformly stirring, centrifuging, and freeze-drying to obtain a pretreatment; melting vaseline, adding the vaseline into the pretreatment, uniformly stirring, and obtaining a hybrid ointment; adding the hybrid ointment into the low glass transition temperature mixture, uniformly stirring, and vacuum degassing to obtain the biological glass-containing wound-care ointment. The application can solve the problems of poor interface compatibility between biological glass particles and a polymer matrix, easy ion burst release or no release of the biological glass in the related art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of medical dressing technology, and in particular to a wound dressing containing bioglass, a dressing, and a method for its preparation. Background Technology

[0002] As the epidermis of the human body, the skin plays a vital role in protecting the internal environment and maintaining its stability. The ultimate goal of treating skin injuries is to rebuild the skin barrier function. High-performance medical dressings can provide an environment conducive to wound healing, possessing good biocompatibility and anti-infection capabilities. By covering damaged skin, they create a wound-healing environment and protect the skin. They are a common type of medical device with broad prospects and research potential.

[0003] Commercially available polyurethane film dressings generally only serve as a physical barrier and do not have healing-promoting, antibacterial, or anti-inflammatory functional effects.

[0004] Bioglass / hydrogel composite dressings and bioglass ointment dressings are mostly gel or ointment-like. After being applied to the wound, they still need to be bandaged with traditional dressings to provide an antibacterial and healing environment for a long time. Moreover, bioglass particles have poor interfacial compatibility with the polymer matrix, which can easily lead to burst release of bioglass ions or complete non-release. Summary of the Invention

[0005] This application provides a wound dressing containing bioglass, an application, and a preparation method to solve the problem in related technologies where the bioglass particles have poor interfacial compatibility with the polymer matrix, and the bioglass is prone to burst release or complete non-release.

[0006] In a first aspect, embodiments of this application provide a method for preparing a wound dressing containing biological glass, comprising: Betaine and tannic acid were stirred evenly to obtain a mixture with a low glass transition temperature. The molar ratio of betaine to tannic acid was 1:(18-22). The stirring conditions for betaine and tannic acid included: vacuum stirring at 65-90℃ for 30-85 min; the Tg of the mixture with a low glass transition temperature was ≤5℃; and the viscosity of the mixture with a low glass transition temperature was 8000-10000 cP at 25℃. Bioglass is added to CaCl2 solution, stirred evenly, centrifuged and freeze-dried to obtain a pretreated product. The bioglass includes at least one of 45S5 bioglass and 13-93 bioglass. After melting petroleum jelly, it is added to the pretreated material and stirred evenly to obtain a hybrid paste; The hybrid ointment was added to the mixture with a low glass transition temperature, stirred evenly, and degassed under vacuum to obtain a wound ointment containing bio-glass.

[0007] In conjunction with the first aspect, in one embodiment, the bioglass has a particle size of 20–45 µm.

[0008] In conjunction with the first aspect, in one embodiment, the concentration of the CaCl2 solution is 0.1–0.2 mol / L; And / or, the mass ratio of bioglass to CaCl2 solution is 1:(4-19).

[0009] In conjunction with the first aspect, in one embodiment, the preparation method further includes: The mass ratio of the bio-glass to petroleum jelly is 1:(3-15). And / or, the mass ratio of the hybrid grease to the mixture with a low glass transition temperature is (2-8):1.

[0010] In conjunction with the first aspect, in one embodiment, the stirring conditions for the bioglass and CaCl2 solution include: stirring at 25–35°C for 10–30 min; And / or, the mixing conditions for petroleum jelly and the pretreated material include: mixing at 1500–5000 rpm for 2–15 min, cooling to 38–41°C and holding at that temperature.

[0011] In conjunction with the first aspect, in one embodiment, the stirring conditions for the hybrid paste and the low glass transition temperature mixture include: pouring the 38-41°C hybrid paste into the 60°C low glass transition temperature mixture and stirring at 550-850 rpm for 2-8 minutes.

[0012] In conjunction with the first aspect, in one embodiment, the preparation method further includes: While mixing betaine and tannic acid evenly, add a 0.5wt% citric acid solution to adjust the pH to 5.5.

[0013] Secondly, embodiments of this application provide a wound dressing containing bio-glass, which is prepared using any of the above-described methods for preparing wound dressings containing bio-glass.

[0014] Thirdly, embodiments of this application provide a wound dressing containing bio-glass, which includes a backing layer, an ointment layer, and a release film stacked sequentially, wherein the ointment layer is a wound dressing containing bio-glass as described above.

[0015] Fourthly, embodiments of this application provide a method for preparing a wound dressing containing bio-glass, comprising: The backing layer is made of non-woven fabric and is treated with corona discharge. The vacuum-de-bubbled ointment containing bio-glass was applied to the backing layer, and after air cooling, a release film was attached.

[0016] The beneficial effects of the technical solution provided in this application include: This application provides a wound dressing containing bioglass, a dressing, and a preparation method. This application achieves strong interfacial bonding between bioglass and the substrate through the construction of a hydrogen bond network with a low glass transition temperature, surface modification of bioglass with calcium ions, and hybrid emulsification with petrolatum. It enables controlled ion release and a peel strength of over 3 N / cm, and has hemostatic, occlusive, antibacterial, and healing-promoting effects. It solves the problems of poor compatibility, uncontrolled ion release, and easy secondary trauma after peeling of traditional bioglass dressings. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 This is a flowchart illustrating the preparation method of the bio-glass wound ointment of this application; Figure 2 The infrared spectrum of the bioglass-containing wound dressing of this application after immersion in SBF human body simulated fluid for 24 hours. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0020] See Figure 1 As shown in the embodiments of this application, a method for preparing a wound ointment containing biological glass is provided, which includes the following steps: 101: Stir betaine and tannic acid evenly to obtain a mixture with a low glass transition temperature.

[0021] In step 101, the molar ratio of betaine to tannic acid is 1:(18-22). This embodiment utilizes an ultra-high proportion of tannic acid, allowing it to function as both a hydrogen bond donor and a polyphenol crosslinking agent, achieving a low glass transition temperature without the need for additional solvents such as propylene glycol. Too low a proportion can lead to an incomplete hydrogen bond network and easy curing; too high a proportion can reduce the density of phenolic hydroxyl groups, weakening the anchoring ability and antioxidant effect on the bioglass. This proportion balances rheology, stability, and bioactivity, ensuring the patch's responsiveness and healing properties.

[0022] The stirring conditions for betaine and tannic acid include: vacuum stirring at 65–90°C for 30–85 minutes. In this embodiment, this temperature (65–90°C) ensures that the tannic acid fully melts and forms a stable hydrogen bond network with the betaine. Too low a temperature can lead to incomplete reaction, while too high a temperature can cause oxidative degradation. Vacuum stirring removes moisture and air bubbles, preventing interference with hydrogen bond formation and ensuring the homogeneity of the mixture with a low glass transition temperature. The 30–85 minute stirring time ensures thorough mixing and complete network construction; too short a time results in uneven dispersion, while too long a time affects activity.

[0023] The low glass transition temperature mixture has a Tg ≤ 5℃ (measured by differential scanning calorimetry DSC) and a viscosity of 8000–10000 cP at 25℃. Too low a viscosity leads to sagging, making thickness control difficult and causing bioglass to settle easily; too high a viscosity results in high coating resistance and defects. Therefore, this application achieves a viscosity of 8000–10000 cP at 25℃ for the low glass transition temperature mixture through the aforementioned molar ratio and stirring conditions. This range balances flowability and retention, ensuring uniform dispersion of bioglass in the slurry at 25℃ without heating, while maintaining a stable hydrogen bond network in the low glass transition temperature mixture to ensure subsequent curing and ion release performance, ultimately effectively meeting the needs of industrial production.

[0024] 102: Add bioglass to CaCl2 solution, stir well, centrifuge and freeze dry to obtain pretreated material.

[0025] In step 102, the bioglass comprises at least one of 45S5 bioglass and 13-93 bioglass. 45S5 bioglass exhibits excellent biocompatibility and osteoconductivity, while 13-93 bioglass degrades faster and has controllable ion release. Both can release Ca. 2+ / Si 4+ Ions stimulate angiogenesis and inhibit bacteria. Using at least one type ensures the dressing possesses good healing-promoting and antibacterial properties, adapting to different wound repair needs and enhancing treatment effectiveness.

[0026] The particle size of the bioglass is 20–45 µm. In this embodiment, the particle size was selected as 20–45 µm to balance the ion release rate and dispersion stability. Too small a particle size can easily lead to ion burst release and cytotoxicity, while too large a particle size affects the uniformity of application and wound adhesion. This range ensures that the bioglass is evenly distributed during application, avoids sedimentation, and simultaneously guarantees Ca2+ distribution. 2+ / Si 4+ Controlled ion release optimizes healing effects.

[0027] The concentration of the CaCl2 solution was 0.1–0.2 mol / L. In this embodiment, a CaCl2 solution with a concentration of 0.1–0.2 mol / L optimized the enrichment of calcium ions on the surface of the bioglass. Too low a concentration would affect anchoring; too high a concentration would easily lead to salt crystallization, increasing osmotic pressure and irritating the wound. This concentration ensured sufficient surface modification, enhanced the binding force with tannic acid, prevented particle aggregation, and guaranteed sustained ion release.

[0028] The mass ratio of bioglass to CaCl2 solution is 1:(4-19).

[0029] The stirring conditions for bioglass and CaCl2 solution include: stirring at 25–35°C for 10–30 min. 25–35°C is a mild, room-temperature range; high temperatures should be avoided to prevent damage to the surface structure of the bioglass or premature reaction. Stirring for 10–30 min ensures the CaCl2 solution is properly stirred. 2+ It fully adsorbs onto the glass surface, forming a stable modified layer. Too short a time results in uneven modification, while too long a time may lead to premature glass degradation. This condition balances modification efficiency and material integrity, providing an ideal interface for subsequent shear emulsification and anchoring, ensuring excellent adhesion performance.

[0030] In step 102, the surface modifier Ca 2+ Si-O on the surface of bioglass - They combine to form Si-O-Ca + The layer lowers the zeta potential, reduces particle aggregation, and coordinates with the phenolic hydroxyl groups of tannic acid to achieve chemical bonding rather than physical blending, thereby improving interfacial compatibility. This is achieved by pre-depositing Ca on the surface of bioglass. 2+ This forms an ion pool, which can extend the lifespan of Si. 4+ / Ca 2+ / P 5+ The release cycle is controlled to avoid sudden release. Furthermore, Ca... 2+ As a salt template during the freeze-drying process, it can maintain the three-dimensional structure of bioglass and prevent collapse. Furthermore, the weakly acidic CaCl2 solution can neutralize the alkalinity of the bioglass, avoiding irritation to the wound surface. Finally, Ca... 2+ It is a clotting factor that can participate in blood clotting, thus giving the dressing its initial hemostatic function.

[0031] As can be seen, in step 102, the Ca in the CaCl2 solution is removed by freeze-drying. 2+ Anchored on the surface of bio-glass, forming Si-O-Ca +The coordination layer, rather than simple physical adsorption, removes water during freeze-drying. After the ice crystals sublimate, mesopores / macropores remain, increasing the specific surface area of ​​the bioglass. This facilitates subsequent petrolatum penetration and sustained ion release. By removing free water, phase separation is prevented when mixing with petrolatum. Furthermore, the bioglass begins ion release immediately upon contact with water, and freeze-drying can pause this process, maintaining its activity until the application stage. During application, wound exudate containing proteases and water penetrates into the low glass transition temperature mixture. Tannins are released through enzymatic / hydrolytic hydrolysis, exposing the bioglass and initiating ion release. Initially, petrolatum acts as a barrier, resulting in slow ion release to prevent burst release and reduce pain. In the middle stage, the low glass transition temperature mixture gradually swells, allowing the bioglass to contact the wound and continuously release ions. In the later stage, the bioglass is fully exposed but dispersed by the low glass transition temperature mixture network, ensuring uniform release.

[0032] 103: After melting the petroleum jelly, add it to the pretreated material and stir evenly to obtain a hybrid grease.

[0033] In step 103, the mass ratio of the bio-glass to petrolatum is 1:(3-15). This ratio is set to balance fluidity and bioactivity. Too much bio-glass will make the paste viscous and difficult to spread, and prone to clumping; too much petrolatum will dilute the bioactivity and result in insufficient ion release. The 1:(3-15) ratio ensures the paste has suitable fluidity at 38-41°C, guaranteeing sufficient bio-glass content to achieve sustained healing and antibacterial effects.

[0034] The mixing conditions for petroleum jelly and the pretreated material include: stirring at 1500–5000 rpm for 2–15 minutes, followed by cooling to 38–41°C and holding at that temperature. A stirring speed of 1500–5000 rpm ensures uniform dispersion of the bio-glass in the petroleum jelly, preventing sedimentation and agglomeration, while also preventing excessive air bubbles from being introduced by high-speed stirring. 2–15 minutes ensures thorough mixing.

[0035] In this embodiment, petrolatum acts as a hydrophobic barrier, encapsulating the pretreated bioglass to form ointment microregions. These microregions and the low glass transition temperature mixture achieve a compatible interface through the amphiphilic nature of betaine (containing both positive and negative charges), preventing phase separation.

[0036] 104: Add the hybrid ointment to the mixture with a low glass transition temperature, stir evenly, and degas under vacuum to obtain a wound ointment containing bio-glass.

[0037] In step 104, the mass ratio of the hybrid ointment to the low glass transition temperature mixture is (2–8):1. This ratio balances the oil-water phase structure. Too much ointment disrupts the hydrogen bond network of the low glass transition temperature mixture, reducing peel strength; too little results in insufficient bioactivity. The (2–8):1 ratio ensures the formation of a stable emulsion, balancing the sealing and moisturizing functions of petrolatum with the healing-promoting functions of bioglass, maintaining the cohesion and adhesion of the dressing, and achieving responsive and long-lasting care.

[0038] The mixing conditions for the hybrid grease and the low glass transition temperature mixture include: pouring the hybrid grease at 38–41°C into the low glass transition temperature mixture at 60°C, and mixing at 550–850 rpm for 2–8 minutes. The temperature difference design ensures matching flowability between the two phases; 60°C reduces the viscosity of the low glass transition temperature mixture, facilitating dispersion; 38–41°C prevents premature solidification of petrolatum or damage to the bioglass. 550–850 rpm provides suitable shear force, promoting uniform distribution of the oil phase micro-regions while avoiding disruption of the hydrogen bond network or introduction of air bubbles. 2–8 minutes ensures sufficient coordination and anchoring of tannic acid to the bioglass surface, forming a stable interface and ensuring sustained ion release and adhesive mechanical properties.

[0039] In step 104, after vacuum degassing, a non-woven fabric is used as a backing layer and subjected to corona treatment; the degassed biological glass-containing wound dressing is applied to the backing layer, cooled by air, and then a release film is attached to obtain the biological glass-containing wound dressing.

[0040] PP / PE nonwoven fabric can be used as the backing layer, and corona treatment is applied to achieve a corona value of 42 dyn / cm. The coating thickness can be set according to actual needs. The scraper of the coating equipment is adjusted to a thickness of 300µm and the forward speed is 0.5m / min. After air cooling at 25℃ for 5 minutes, the dressing is formed. After winding, it is cut and a release film is attached, and the dressing preparation is complete.

[0041] At room temperature, immerse the bio-glass-containing wound dressing in SBF human body fluid for 24 hours. See also Figure 2 The image shown is an infrared spectrum of the bioglass after being immersed in SBF human body fluid. From... Figure 2 As can be seen, a characteristic double peak of 601.68 cm⁻¹ of hydroxyapatite-like material is produced in simulated body fluid. -1 563.50cm -1 This proves that hydroxyapatite-like material is formed, which in turn proves that the wound dressing of this application is bioactive.

[0042] Example 1 A method for preparing a wound dressing containing bio-glass includes: The raw materials were weighed according to a betaine:tannic acid molar ratio of 1:20, and stirred under vacuum at 90°C for 30 min to obtain a dark brown supercooled liquid with a viscosity of 10000 cP at 25°C, namely the low glass transition temperature mixture LTTM.

[0043] Bioglass pretreatment: Take 5g of 45S5 bioglass (particle size 20-45μm), add 50mL of 0.1mol / L CaCl2 solution, stir at 25℃ for 10min, centrifuge and freeze dry to obtain the pretreated material.

[0044] Preparation of hybrid grease: 15g of petroleum jelly was melted at 65℃, the pretreated material was added, homogenized at 5000rpm for 2min, cooled to 40℃ and kept warm, and the mass ratio of bioglass to petroleum jelly was 1:3.

[0045] Hybrid molding: Pour the 40℃ hybrid grease into the 60℃ low glass transition temperature mixture, stir at 700 rpm for 5 min, and vacuum degas for 3 min; corona treat PP / PE nonwoven fabric to 42 dyn / cm, apply with a doctor blade at 300 μm and speed of 0.5 m / min, and air cool at 25℃ for 5 min to form the final product. The mass ratio of the hybrid grease to the low glass transition temperature mixture is 5:1.

[0046] The coating thickness is 205 μm, the peel strength is 3.1 N / cm, and the Ca content is [missing information - likely a value or value] after 24 hours. 2+ Released 11.4 ppm, DPPH clearance rate 83%, L929 cell viability 89%.

[0047] The standard test method for peel strength is a 180° peel test at a speed of 300 mm / min, with the average peel force per centimeter as the indicator. For details, refer to "GB / T 2792-2014 Test Method for Peel Strength of Adhesive Tapes".

[0048] Ca at 24h 2+ Release was measured by testing Ca after soaking the patch for 24 hours. 2+ Prepare the solution with 1:50 deionized water, shake and soak at 37℃ for 24 hours, filter and take the supernatant, and calculate the calcium ion concentration by atomic absorption spectrophotometry and standard curve.

[0049] DPPH scavenging rate: Prepare a 0.1 mmol / L DPPH ethanol solution, react it with the extract of the patch sample in the dark for 30 min, and then measure the absorbance at a wavelength of 517 nm. Calculate the scavenging rate using the following formula: Scavenging rate (%) = (1 - (As - Ab) / Ac) × 100%, where As is the absorbance of the patch sample extract after reacting with 0.1 mmol / L DPPH ethanol solution in the dark, Ab is the absorbance of the patch sample extract after reacting with ethanol in the dark, and Ac is the absorbance of ethanol after reacting with 0.1 mmol / L DPPH ethanol solution in the dark.

[0050] Cytotoxicity: L929 mouse fibroblasts were used. After 24 hours of MTT reaction, the absorbance was measured using an ELISA reader. Cell viability ≥70% confirmed the absence of cytotoxicity. The specific method is as follows: Sample extract preparation: According to ISO 10993-5, take the patch sample and add serum-free DMEM medium at a solid-liquid ratio of 0.1 g / mL. Incubate in a 37℃ constant temperature shaking incubator for 24 h. After extraction, filter through a 0.22 μm microporous membrane to remove bacteria and obtain the stock extract, which will be used as the test solution for the experimental group.

[0051] Cell seeding: L929 cells in logarithmic growth phase were digested with trypsin and then prepared into a 1×10⁻⁶ m³ / h culture medium. 4 ~1×10 5 Cell suspension of cells / mL. Inoculate each well of a 96-well plate with 100 μL of cell suspension and incubate in a CO2 incubator at 37°C and 5% CO2 saturated humidity for 24 h until the cells adhere and reach 70%–80% confluence.

[0052] Sample addition and incubation: Remove the original culture medium from the 96-well plate. Add 100 μL of the original extract to each well of the experimental group; add 100 μL of fresh complete culture medium to the negative control group; add 100 μL of complete culture medium containing 10% DMSO to the positive control group. Set up 6 replicates for each group, and place the culture plate back into the CO2 incubator for 24 h of incubation.

[0053] MTT reaction and color development: After 24 h of incubation, add 20 μL of 5 mg / mL MTT solution to each well and return to the CO2 incubator for another 4 h of incubation. After incubation, carefully aspirate the supernatant from the wells, add 150 μL of DMSO to each well, and place on a shaker to shake at low speed for 10 min to completely dissolve the formazan crystals.

[0054] Absorbance detection and calculation: The absorbance (OD value) of each well was measured at a wavelength of 490 nm using an ELISA reader, and the average OD value of each replicate was used for calculation.

[0055] Formula for calculating cell viability: Cell viability (%) = mean OD value of experimental group / mean OD value of negative control group × 100%.

[0056] In this experiment, the L929 cell viability of the dressing group was 89%. According to the ISO 10993-5 standard, the cell viability of this sample is ≥70%, with no obvious cytotoxicity, which meets the biocompatibility requirements for medical dressings.

[0057] Example 2 (with citric acid modification) The difference from Example 1 is that when preparing LTTM, a 0.5 wt% citric acid solution was added to adjust the pH to 5.5.

[0058] The antioxidant half-life of tannic acid was extended from 8 h to 16 h, the peel strength was 3.1 N / cm, and the Ca2+ content was reduced at 24 h. 2+ Released 11.4 ppm, DPPH clearance rate 83%, L929 cell viability 89%.

[0059] Citric acid helps stabilize tannic acid in an acidic environment, extending its half-life and delaying oxidation, resulting in more consistent product quality. The longer half-life allows tannic acid to continuously scavenge free radicals and reduce oxidative stress damage in the wound environment, thus reducing wound inflammation and promoting skin tissue repair. Simultaneously, improved antioxidant stability helps reduce the oxidative degradation of the active ingredients during storage and use, enhancing the overall stability and lifespan of the product. This ensures the dressing provides stable antioxidant and wound protection throughout its application cycle, further optimizing its biocompatibility and clinical efficacy.

[0060] Example 3 The difference from Example 1 is that 45S5 bioglass is replaced with 13-93 bioglass.

[0061] Fibroblast collagen secretion increased by 32%, and peel strength was 2.9 N / cm.

[0062] Comparative Example 1 (mixture without low glass transition temperature) Hydrogels are used to replace mixtures with low glass transition temperatures.

[0063] Bio-glass particles showed severe aggregation, and Ca2+ levels were observed at 24 hours. 2+ It releases 28 ppm of liquid, has a peel strength of only 0.8 N / cm, a DPPH scavenging rate of 45%, and its ion release is uncontrollable.

[0064] Comparative Example 2 (without CaCl2 pretreatment) The difference from Example 1 is that the bioglass is not modified with CaCl2 solution and is directly mixed with petrolatum. The other raw materials, proportions and processes are the same as in Example 1.

[0065] Bioglass surface Ca 2+ It has low density, a peel strength of 1.5 N / cm, and uneven ion release, with a burst release in the early stage and stagnation in the later stage.

[0066] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for preparing a wound ointment containing biological glass, characterized in that, It includes: Betaine and tannic acid were stirred evenly to obtain a mixture with a low glass transition temperature. The molar ratio of betaine to tannic acid was 1:(18-22). The stirring conditions for betaine and tannic acid included: vacuum stirring at 65-90℃ for 30-85 min; the Tg of the mixture with a low glass transition temperature was ≤5℃; and the viscosity of the mixture with a low glass transition temperature was 8000-10000 cP at 25℃. Bioglass was added to a CaCl2 solution, stirred until homogeneous, centrifuged, and then freeze-dried to obtain a pretreated product. The bioglass included at least one of 45S5 bioglass and 13-93 bioglass. The concentration of the CaCl2 solution was 0.1–0.2 mol / L. The stirring conditions for the bioglass and CaCl2 solution included: stirring at 25–35°C for 10–30 min. The particle size of the bioglass was 20–45 µm, and the mass ratio of the bioglass to the CaCl2 solution was 1:(4–19). After melting petroleum jelly, it is added to the pretreated material and stirred evenly to obtain a hybrid paste; the mass ratio of the bio-glass to petroleum jelly is 1:(3-15). The hybrid ointment was added to the low glass transition temperature mixture, stirred evenly, and degassed under vacuum to obtain a wound ointment containing bioglass. The mass ratio of the hybrid ointment to the low glass transition temperature mixture was (2-8):

1. The stirring conditions for the hybrid ointment and the low glass transition temperature mixture included: pouring the 38-41℃ hybrid ointment into the 60℃ low glass transition temperature mixture and stirring at 550-850 rpm for 2-8 minutes.

2. The method for preparing the ointment containing biological glass as described in claim 1, characterized in that: The mixing conditions for petroleum jelly and the pretreated material include: mixing at 1500–5000 rpm for 2–15 minutes, cooling to 38–41°C and holding at that temperature.

3. The method for preparing the ointment containing biological glass as described in claim 1, characterized in that, The preparation method further includes: during the process of stirring betaine and tannic acid evenly, adding a 0.5wt% citric acid solution to adjust the pH to 5.

5.

4. A wound-healing ointment containing biological glass, characterized in that: It is prepared using the preparation method of the ointment containing biological glass as described in any one of claims 1 to 3.

5. A wound dressing containing bio-glass, characterized in that: It comprises a backing layer, an ointment layer, and a release film stacked sequentially, wherein the ointment layer is a wound ointment containing bio-glass as described in claim 4.

6. A method for preparing a wound dressing containing bio-glass as described in claim 5, characterized in that, It includes: The non-woven fabric is used as the backing layer and is treated with corona discharge. The vacuum-de-bubbled ointment containing bio-glass was applied to the backing layer, and after air cooling, a release film was attached.

Citation Information

Patent Citations

  • Powder and process

    WO2018025020A1

  • Boron-containing bioactive glass, and preparation method therefor and use thereof

    WO2024207695A1